Uterine artery embolisation in symptomatic patients with placenta accreta spectrum disorders - Brustman, David; Raupach, Jan; Chovanec, Vendelin; Ryska, Pavel (Biomedical papers, 2024)
Objectives. Postpartum haemorrhage is the most common cause of mortality among women after childbirth. Therefore, this work aims to highlight the possibility of endovascular treatment of postpartum haemorrhage due to remnants in patients with placenta accreta spectrum disorders (PAS disorders) using selective UAE after failure of the standard management. This procedure is a relatively safe and technically nondemanding, with a low risk of recurrent vaginal bleeding.Materials and Methods. This article presents an evaluation of the results of eight patients (age between 19-39 years) who underwent selective transarterial embolisation of uterine arteries from January 2022 to August 2023 at the angio-interventional department of our university hospital center. Based on a multidisciplinary consensus of sonographically detected residues of placenta accreta with typical hypervascularisation, unilateral/bilateral embolisation of the uterine artery was performed with a microcatheter using polyvinyl alcohol embolisation particles, possibly in combination with gelatine foam.Results. There were no periprocedural complications during embolisation, nor were there episodes of repeated bleeding or other postprocedural complications during the follow-up. Two patients underwent surgical revision of the uterine cavity with extirpation of devascularised residual tissue.Conclusions. Thus far, this procedure has proven to be a safe and relatively technically nondemanding method supplementing the management of symptomatic patients with PAS disorders with a low risk of rebleeding.
Keywords: uterine artery embolisation; endovascular treatment; postpartum haemorrhage; retained placenta; placenta accrete